2014
DOI: 10.1093/heapro/dat092
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building in indigenous men's groups and sheds across Australia

Abstract: This article presents an investigation into capacity building, at the community level, in Aboriginal and Torres Strait Islander Men's Groups and Sheds. As safe men's spaces, Men's Groups and Sheds represent an ever-growing social, and health and well-being community service across Australia. The study is qualitative and employs 'yarning circles' (focus groups), semi-structured interviews and observations to gather data from 15 Groups/Sheds involving 45 men from urban, regional and remote communities. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Programs without these elements were considered inadequate. A Men's Shed program provided a responsive example of this: “some men didn't even have birth certificates so we negotiated with the service, bought them into the Shed and got the men sorted out … same for men who didn't have a driver's license” APQ (Southcombe et al, ). Outreach was a positive element in programs, but this needed to be relevant and have specifically appropriate services (Fitts & Palk, ).…”
Section: Resultsmentioning
confidence: 99%
“…Programs without these elements were considered inadequate. A Men's Shed program provided a responsive example of this: “some men didn't even have birth certificates so we negotiated with the service, bought them into the Shed and got the men sorted out … same for men who didn't have a driver's license” APQ (Southcombe et al, ). Outreach was a positive element in programs, but this needed to be relevant and have specifically appropriate services (Fitts & Palk, ).…”
Section: Resultsmentioning
confidence: 99%
“…One study revealed that reduced pressure to adhere to work-related identities and an inclusive environment were seen as beneficial by Men's Sheds members living with disabilities (Hansji, Wilson and Cordier 2015 ). Men's Sheds have also been identified as an effective way to promote health and to reduce barriers to health and social services for Indigenous men who preferred to access health information at men's groups rather than traditional health-care settings (Southcombe, Cavanagh and Bartram 2014 ). It is also important to examine factors affecting involvement in sheds outside Australia, Ireland, the UK and New Zealand, where sheds have the longest history and greatest availability and recognition (Golding 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…While being welcoming and open is a clear goal of the Men’s Sheds movement ( Golding, 2015 ), this particularly narrow demographic could also result in promoting another “old boys club” which excludes and limits its true potential. Canada and other countries where the Men’s Sheds movement is emerging could benefit from learning about capacity building in indigenous Men’s Sheds in Australia ( Southcombe, Cavanagh, & Bartram, 2015 ). With nearly 1,000 sheds operating in Australia and a growing international Men’s Sheds movement, it will be important for men to consider how they are promoting this movement, and whether those methods promote or restrict diversity (at least in terms of sexual and racial/ethnic diversity discussed in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, although the Men’s Sheds participants in the present study tended to promote hegemonic masculinity practices, the men also demonstrated that counternarratives and practices can be, and indeed are, welcomed once relationships and trust have been established. However, Men’s Sheds could perhaps benefit from expanding further to attract more diverse groups reflective of the wider community, following examples of capacity building within Aboriginal and indigenous communities in Australia ( Southcombe et al, 2015 ). Although the Beyond Blue report ( Flood & Blair, 2013 ) indicates that Men’s Sheds are diverse organizations in many respects (e.g., they are both urban and rural, they focus on disparate activities, and they attract men of all ages), we are not aware of demographic research to date reporting on the prevalence of sexual or racial/ethnic diversity within and among sheds.…”
Section: Discussionmentioning
confidence: 99%